Nineteen eighty-four - Orwell, George (London : Penguin Books, 1988)
In "Nineteen eighty-four", one of the 20th century's great myth-makers George Orwell takes a cold look at the future. "Hidden away in the Record Department of the sprawling Ministry of Truth, Winston Smith skilfully rewrites the past to suit the needs of the Party. Yet he inwardly rebels against the totalitarian world he lives in, which demands absolute obedience and controls him through the all-seeing telescreens and the watchful eye of Big Brother, symbolic head of the Party. In his longing for truth and liberty, Smith begins a secret love affair with a fellow-worker Julia, but soon discovers the true price of freedom is betrayal."
Keywords: Classical literature; Control (Psychology) Fiction